Pelatihan Pembuatan Sistem Informasi Desa Berbasis Website Pada Desa Sei Mencirim Kecamatan Kutalimbaru - Putri Harliana; Nenna Irsa Syahputri; Adidtya Perdana; Mardiana (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
In the current digital era, the administrative system that still uses the conventional (manual) method is very outdated. Especially in the case of the village administration system as a provider of information services where the conventional method is an inefficient and costly way. The demand for fast, precise and accurate village information services is the reason why it is necessary to implement a web-based village information system. Ease of management and speed of transactions such as writing letters at the village office are other supporting reasons. To support these reasons, the use of a web-based village information system seems to have become a necessity to avoid errors, such as letters that have been made but have not been recorded. And as an effort to integrate manual and electronic procedures, a combination of human and machine work systems. With the existence of a web-based village information system, village communities are expected to get convenience in making letters or administration because the process is easier and more efficient.